Estruturação longitudinal da ictiofauna a jusante das Cataratas do Iguaçu - Santos, Dhonatan Oliveira dos (2013)
This study evaluated the distribution and structure of the ichthyofauna of the Iguaçu River, in the stretch between downstream of the Iguaçu Falls to the mouth of the Paraná River. Were sampled monthly during the period of October 2010 to September 2012 using gillnets and longlines. Environmental variables showed no statistical differences between the sampled points. Were collected 10,996 fish belonging to 124 species, the Siluriformes had the greater values of richness, while Characiformes were the most abundant. Were recorded 17 species of longdistance migratory. In the lower portion were recorded high values of relative abundance for small species, while the upper portion, were recorded high values of biomass for large species. The evenness and Shannon diversity index showed significant differences between the points of the lower and upper portion, indicating that there could be some dominant species. The pattern increment longitudinal in richness was not detected, and the points of the upper portion were separated from others in multiple comparison test, suggesting a structuring for areas along the stretch sampled. These results indicate that the stretch of Iguaçu river, between Iguaçu Falls to the mouth with the Paraná River, the ichthyofauna presents differentiated structure along the spatial gradient, which may be related to differences in the physical structure of the sampled area